Group psychological intervention for postnatal depression: a nested qualitative study with British South Asian women - Masood, Yumna (BMC Womens Health, 2015)
BACKGROUND: Postnatal depression affects 10–15 % of all mothers in Western societies and remains a major public health concern for women from diverse cultures. British Pakistani and Indian women have a higher prevalence of depression in comparison to their white counterparts. Research has shown that culturally adapted interventions using Cognitive Behavioural Therapy (CBT) may be acceptable and may help to address the needs of this population. The aim of this study was to assess the acceptability and overall experience of the Positive Health Programme by British South Asian mothers. METHODS: This was a nested qualitative study, part of an exploratory randomized controlled trial (RCT) conducted to test the feasibility and acceptability of a culturally-adapted intervention (Positive Health Programme or PHP) for postnatal depression in British South Asian women. In-depth interviews (N = 17) were conducted to determine the views of the participants on the feasibility and acceptability of the intervention. RESULTS: The participants found the intervention acceptable and experienced an overall positive change in their attitudes, behaviour, and increased self-confidence. CONCLUSIONS: The findings suggest that the culturally adapted Positive Health Programme is acceptable to British South Asian women. These results support that culturally sensitive interventions may lead to better health outcomes and overall satisfaction. TRIAL REGISTRATION: Protocol registered on Clinicaltrials.gov NCT01838889